2020
DOI: 10.1016/j.foodcont.2019.106969
|View full text |Cite
|
Sign up to set email alerts
|

Lacto-fermented Kenaf (Hibiscus cannabinus L.) seed protein as a source of bioactive peptides and their applications as natural preservatives

Abstract: Kenaf seeds are a promising source of natural preservatives for food applications due to their potential as a substrate to generate peptides with high antibacterial activity. We sought to generate bioactive peptides with antibacterial activity from Kenaf seed proteins via lactofermentation. The ground seeds were defatted and protein extracted using acid precipitation. Kenaf seed protein was fermented with Lactobacillus casei for 72 h at 37 °C, and the antibacterial activity, MIC, and MBC were determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…Different concentrations of antifungal metabolites, such as organic acids and bioactive peptides on the fruit surface, might reduce the disease incidence in treated mango. The selected CFS reduced disease incidence to a different extent, due to their ability to inhibit mycelia growth and/or conidia germination [ 16 , 34 , 35 ]. The highest reduction in disease incidence was observed with both CFS that is produced by L. fermentum ATCC9338 on PKC and PP, which exhibited higher antifungal activities, as well as lower pH and high peptide concentrations, suggesting that the reduction in disease incidence may be due to the production of antifungal compounds, such as organic acids and bioactive peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different concentrations of antifungal metabolites, such as organic acids and bioactive peptides on the fruit surface, might reduce the disease incidence in treated mango. The selected CFS reduced disease incidence to a different extent, due to their ability to inhibit mycelia growth and/or conidia germination [ 16 , 34 , 35 ]. The highest reduction in disease incidence was observed with both CFS that is produced by L. fermentum ATCC9338 on PKC and PP, which exhibited higher antifungal activities, as well as lower pH and high peptide concentrations, suggesting that the reduction in disease incidence may be due to the production of antifungal compounds, such as organic acids and bioactive peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Svanström et al [ 35 ] described that the organic acids are responsible for the inhibition of conidia production of filamentous fungi. In other studies, Kwak et al [ 38 ], Arulrajah et al [ 34 ], and Liu et al [ 39 ] suggested that bioactive peptides are responsible for the control of conidia production, inhibit conidial germination, induce conidia death, and inhibit the mycelia growth. Taken together, we suggest that the conidia production was inhibited by organic acids and bioactive peptides that are produced by LAB in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Fermented soy-based foods have also been found to produce bioactive peptides with antidiabetic and ACE inhibitory effects [ 76 ]. Arulrajah et al conducted a study on the properties of kenaf seed proteins fermented by Lacticaseibacillus casei [ 95 ]. After the fermentation process, the proteins were fractionated and peptides were identified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several enzymes of different origin are also used to isolate new, most often short-chain, peptides. Before hydrolysis, the source of peptides may be subjected to various processes, e.g., fermentation [ 9 , 10 , 11 ]. Biopeptides can also be synthesized chemically [ 12 , 13 , 14 ] or can be obtained through the expression of appropriate genes [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%